The Effect of Livestock Ownership and Educational Level on the Economic Welfare of Goat Farmers in Kedungbanteng District - Krismiwati Muatip; Muhammad Alief Bhesara; Sri Mastuti (Jurnal Online Pertanian Tropik, 2025)
This study aims to examine the number of goats owned and the education levels of breeders in Kedungbanteng District, to assess their economic welfare, and to analyze the influence of livestock numbers and education on the welfare of goat farmers. Kedungbanteng District was selected using purposive sampling due to its relatively high poverty rate in Banyumas Regency. Villages were sampled randomly, representing 50% of the district’s total villages: Beji, Karangnangka, Kedungbanteng, Dawuhan Kulon, Kebocoran, Dawuhan Wetan, and Melung.A total of 77 goat breeders were selected as respondents using the Slovin formula and random sampling. Data were analyzed through quantitative descriptive analysis, NTPRP, and multiple linear regression. The results showed that breeders owned an average of 5.67 goats, had an average of 7.27 years of formal education, and achieved an average welfare level of 1.49. Furthermore, the study found that both the number of livestock owned and the breeders’ education levels significantly influenced their economic welfare.